Activity-based costing method (ABC costing) and profitability at a Peruvian mining company - Vicente Bejarano, Ruth Milagros (2023)
This research seeks to determine how the activity-based costing system (ABC costing) influences the profitability of a small polymetallic mining company, using a hypothetical deductive methodology, with an applied quantitative approach, non-experimental design, and causal correlational level. The population consists of 84 monthly cost reports and financial statements from 2015 to 2021 and the census-type sample consists of 83 reports, except for the month of April 2020 as a result of the stoppage due to COVID-19 restrictions. The result of a general hypothesis test using regression statistics calculated with the SPSS software, determined a Chi-Square value of 9.149 with p = 0.010 < α = 0.05. Therefore, the null hypothesis was rejected, and the alternative hypothesis was accepted. This means that ABC costing has an influence on the studied company’s profitability.